PENGARUH MEDIA AUDIOVISUAL TERHADAP PENGUASAAN KOSAKATA BAHASA INGGRIS SISWA KELAS III SEKOLAH DASAR - Githa Shang Inaa Fa Biola; Mersilina Luther Patintingan (WASIS : Jurnal Ilmiah Pendidikan, 2021)
This study examined the influence of the use of audiovisual media on the level of English vocabulary mastery of grade 3 students at SDN 130 Tokesan Tana Toraja Regency. The approach used in this research is quantitative approach with one group pretest posttest design. Data analysis technique used in this study is using t-test formula.Based on the results of the study obtained showed that with the value of significance of t-test results less than 0.05 is 0.000, and the result of t calculate greater than t table is t count with a value of 6704 greater than the table t value of 2,093, it can be concluded that there is an influence of the use of audiovisual media on the level of Mastery of English vocabulary of grade III students sdn 130 Tokesan Tana Toraja